TECHNOLOGY ORIENTED EFFICIENCY ANALYSES OF R&D COMPANIES: LONGITUDINAL APPROACH - Arici, Tugkan; Özdemir, Aydın; Cigerim, Erşan; Gök, Mehmet Şahin (Faculty of Engineering, University of Kragujevac, 2022)
This study evaluates the efficiency and productivity of technology companies included in the BIST 100 Index and Fortune 500 list using the DEA-Malmquist model. Firstly, technology-oriented efficiency analyses were conducted. In the second stage, we aim to analyze the efficiency trend of longitudinal (panel) data using the Malmquist approach to understand the frontier shift and efficiency changes from 2005 to 2019. R&D expenditure, R&D personnel cost, total personal number, and marketing expenditure were considered as inputs, while total income, export income, and the patent number were considered as outputs. According to the findings, fifteen of twenty-seven firms were on the frontier once, but only three were on the frontier more than three times. Eighteen firms improved in the Malmquist Index (TFPCH) from 2015 to 2019, with the most improvement in 2015-2016. Besides that, in 2019, a performance improvement of seven percent compared to 2015. Furthermore, it is determined that Scale Efficiency scores increase by 0.163 for extra Net Sales of firms. © 2022 Elsevier B.V., All rights reserved.
Keywords: BIST; DEA; Fortune 500; Malmquist Index; Technology Oriented